PENERAPAN AISAS MODEL DALAM KOMUNIKASI PEMASARAN DESA DIGITAL PADA DESA WISATA SERANG KABUPATEN BLITAR - Andiwi Meifilina (KOLONI, 2022)
The role of marketing communications is increasingly important in the development of the tourism sector. The use of digital media in tourism promotion activities continues to grow in line with the increasing number of digital media users in Indonesia. Related to marketing communications in the tourism sector, it is also necessary to pay attention to the implications that arise both for potential tourists and the community around tourist destinations in Tourism VillagesSerang District Panggungrejo Blitar Regency. The use of digital media requires several conditions and also gives birth to implications that must be considered in every message processing because it can have an impact on the recipients of the message, namely the tourism actors in Serang Village, Blitar Regency. This research uses a qualitative approachexplainimplementing and describing the impact of the AISAS Model in Digital Village Marketing communications.In this study, the researcher used purposive sampling technique. The data collection techniques were observation, interviews and documentation. The results of research on the application of the AISAS Model in digital village marketing communicationsinclude: 1. Attention (visitors' attention, knowledge of tourist villages through the media, awareness of tourist villages, visitor's attention to tourism village products, visitor attention through services). 2. Interest (reason for interest in tourist villages through the media). 3. Search (search for information through the media, knowledge of the location and price). 4. Action (decision to visit based on information, decision to visit related to price, distance, facilities, actions related to tourist attractions). 5. Share (friends as tourists and sharing experiences, worth of mouth and visiting experiences, social media as a means of sharing stories. Dlookapplication of the AISAS Model in digital village marketing communicationsespecially in the search, action and share phase where tourists play an active rolethrough social media such as Facebook and Instagram. Keywords: AISAS model, marketing communication, digital village